Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.366
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Methodology for Detecting and Prioritizing Needs during Crisis Events

Abstract: In times of crisis, identifying essential needs is crucial to providing appropriate resources and services to affected entities. Social media platforms such as Twitter contain a vast amount of information about the general public's needs. However, the sparsity of information and the amount of noisy content present a challenge for practitioners to effectively identify relevant information on these platforms. This study proposes two novel methods for two needs detection tasks: 1) extracting a list of needed reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…(Extractive) text summarization identifies the most salient sentences in a corpus (Eisenstein 2019). Needs detection identifies the resources needed during a disaster, e.g., by extracting tweets that mention resources needed (Basu et al 2017) or creating a ranked list of resources (Sarol et al 2020).…”
Section: Impact Of Source Selection On Sii Variationmentioning
confidence: 99%
“…(Extractive) text summarization identifies the most salient sentences in a corpus (Eisenstein 2019). Needs detection identifies the resources needed during a disaster, e.g., by extracting tweets that mention resources needed (Basu et al 2017) or creating a ranked list of resources (Sarol et al 2020).…”
Section: Impact Of Source Selection On Sii Variationmentioning
confidence: 99%
“…During crisis, not only affected people wrote for help also the people who can help and give any available to affected people. Therefore, A semi-automated platform called NARMADA is proposed to collect all social media posts which include all information about assisting post-disaster relief coordination efforts by applying Natural Language Processing and Information Retrieval techniques for detecting the needs and the available need-related resources to match the needs and its suitable resource [12], or detect the needs from social media but using the resources from the official organization and agent like World Health Organization's (WHO) in case of COVID-19 which provide resource planning guidelines by proposing two methods for 2 distinct but related needs detection tasks (1)detect the top needs for COVID19 by using word embedding to obtain the closest terms to needs and supplies(2) Specific needs detection to identify people who needs particular resource by using rule-based methodology [14]. Most of previous related work focus for detecting other details related to crisis not only the type of crisis but also the related sub events and the needs of affected people which is the major purpose in the crisis management process.…”
Section: Related Workmentioning
confidence: 99%
“…However, prior research has shown that at least in some situations, it is important to distinguish between different types of crises, especially man-made versus natural ones, as they require different response strategies to effectively address unique characteristics and challenges (Alexander 2005;Palen et al 2009). Natural crises such as hurricanes, earthquakes, and floods are often unpredictable and require immediate action to save lives and minimize damage (Sarol et al 2020;Sarol, Dinh, and Diesner 2021). Man-made crises such as terrorist attacks or warfare often involve intentional harm or negligence and require approaches involving intelligence, law enforcement, security measures, and efforts to ensure the safety of affected populations (Chang, Diesner, and Carley 2012;Diesner and Carley 2010;Petrescu-Prahova and Butts 2005;Tierney and Trainor 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature in crisis informatics highlights the need for understanding the distinct characteristics and dynamics of different types of crises, including their causes, impact, and response requirements (Olteanu, Vieweg, and Castillo 2015;Sarol et al 2020). Detecting needs related to a crisis, a task driven by advances in natural language processing (NLP), has shown to be effective in reliably identifying specific challenges associated with different crisis events (e.g., and types (e.g., biological disaster) (Sarol et al 2020;Basu et al 2017;Sarol, Dinh, and Diesner 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation